2003
DOI: 10.2225/vol6-issue3-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Enzymological characterization of pineapple extract for potential application in oak tasar (Antheraea proylei J.) silk cocoon cooking and reeling

Abstract: Proteinases have the potential to effect partial solubilization of the proteinaceous gum sericin involved in binding the silk strands together in cocoon, an essential step in the silk cocoon cooking and reeling. Therefore, pineapple extract rich in cysteine proteinases was enzymologically characterized for its potential application in oak tasar (Antheraea proylei J.) silk cocoon cooking and reeling. Optimum sodium carbonate concentration (9.8 mM) and optimum temperature (60ºC) for the proteinase activity were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
2
9
0
Order By: Relevance
“…The fabric degummed with sodium carbonate showed smaller values of 2HG and 2HG5 than those degummed with bromelain ( Table IV). The weight of the fabric degummed with bromelain is larger than that of the sample degummed with alkali solution (Table III), coinciding with the literature that found that high G values correspond to high yarn density and very close contact [25] . The shear hysteresis behavior in the low shear angle region (2HG) value and the 2HG5 value of the enzyme degummed fabric was significantly different to that of the alkali degummed fabric.…”
Section: Shearing Behaviorssupporting
confidence: 89%
See 1 more Smart Citation
“…The fabric degummed with sodium carbonate showed smaller values of 2HG and 2HG5 than those degummed with bromelain ( Table IV). The weight of the fabric degummed with bromelain is larger than that of the sample degummed with alkali solution (Table III), coinciding with the literature that found that high G values correspond to high yarn density and very close contact [25] . The shear hysteresis behavior in the low shear angle region (2HG) value and the 2HG5 value of the enzyme degummed fabric was significantly different to that of the alkali degummed fabric.…”
Section: Shearing Behaviorssupporting
confidence: 89%
“…Stem bromelain consists of abundant applications, including therapeutic [17][18][19], food [20][21][22], cosmetic [23][24], and textile industries [15,[25][26][27][28][29]. In textile industries, bromelain is used for cocoon cooking and reeling processes [25][26], silk degumming process [27][28][29], and proving the dyeing properties of protein fibers without changes in mechanical properties of the fabrics [15]. However, bromelain is usually sufficiently active without the addition of activators [30].…”
Section: Introductionmentioning
confidence: 99%
“…A recent research study by Anwar et al reported that fabric properties were improved when stem bromelain was crosslinked with 0.25 and 1.25% glutaraldehyde (GTA). Similar results were reported by Koh et al and Singh et al Koh et al reported that bromelain can improve the dyeing properties of protein fibres such as silk and wool. They found that bromelain can eliminate impurities and scales in wool and silk, improving dye accessibility while conserving the tensile properties of the fibres.…”
Section: Commercialisation Of Bromelainsupporting
confidence: 89%
“…They found that bromelain can eliminate impurities and scales in wool and silk, improving dye accessibility while conserving the tensile properties of the fibres. Singh et al found that the addition of a pineapple extract with bromelain activity with 9.8 mmol L − 1 sodium carbonate at 60 °C during silk cocoon processing reduced the required softening time from 20 h to only 30 min.…”
Section: Commercialisation Of Bromelainmentioning
confidence: 99%
“…Thus, the development of an effective cocoon cooking method using enzyme treatment will reduce softening time while increasing production and saving energy. For instance, Singh et al (2003) reduced the softening time from 20 h to 30 min using pineapple extract incorporated with 9.8 mM of sodium carbonate at 60°C. Additionally, Koh et al (2006) reported that the pretreatment of silk and wool with bromelain improved tactile behavior and wettability by removing impurities and scale.…”
Section: Textile Industrymentioning
confidence: 99%